Self-presentation and social media usage : a case study of professional alpine skiing athletes during the Winter Olympic Games and World Cup - Schibblock, Vivien (SAGE Business Cases., 2022)
Social media sites are rich communication and marketing tools used by athletes to promote their "brand" and interact with fans. Indeed, the proliferation of social media has led to athletes promoting themselves across multiple platforms. This study examined how the world's top 10 professional alpine skiing athletes used social media to present themselves and engage with fans during the 2017-18 World Cup and 2018 Winter Olympic Games. The data for the latest Winter Olympic Games in 2022 (organized under changed circumstances because of COVID-19) were not available for this study at the time of finalization. Guided by self-presentation theory, this study used a content analysis to examine how athletes presented themselves in social media photographs. The results demonstrated that athletes employed similar posting patterns across the social media platforms (i.e., Facebook, Twitter, and Instagram). The posting distribution per athlete and channel was different, as some athletes used the same posts across all channels. Twitter boasted the highest posting frequency. Based on the coded social media posts, athletes' self-presentation mainly focused on business life content. Thus, they appeared as dressed but posed, a finding that aligns with Goffman's notion of front-stage performance. This case study extends the literature as it involves an analysis of self-presentation across multiple channels, comparing two international events while using a sample of one sport.